A method to improve embryo development potential when fertilization is delayed in mice. (2nd September 2020) - Chu, Dapeng; Wang, Haiping; Fu, Lei; Zhou, Wenhui; Li, Yuan
ABSTRACT: The purpose of this study was to explore the application of glucose to improve embryo development potential when fertilization is delayed in mice. After recovery, mouse oocytes were cultured alone for 6 h before fertilization in three fertilization media: G-IVF PLUS, G-IVF PLUS with 5 mM and 10 mM glucose. G-IVF PLUS group was used as the control group. Then, in vitro fertilization (IVF) was performed and blastocysts were transferred at Day 4. To compare the effects of different glucose concentrations on embryo development and birth outcomes, conventional IVF and embryo transfer were carried out in G-IVF PLUS, G-IVF PLUS with 5 mM and 10 mM glucose. The results indicated that G-IVF PLUS with 5 mM glucose significantly increased blastocyst rate ( p < 0.05) and birth rate ( p < 0.05) when fertilization was delayed 6 h compared with G-IVF PLUS groups. In conventional IVF without delayed fertilization, embryo development was not significantly affected by G-IVF PLUS with 5 mM or 10 mM glucose. There were no significant differences in terms of birth rate, fetal weight, crown-rump length, tail length and birth defect rate among the three groups. In conclusion, 5 mM glucose could significantly improve embryo developmental potential and birth outcomes when fertilization was delayed 6 h and did not have adverse effects on embryo quality and birth outcomes for normal IVF. It might have a good prospect of clinical application in assisted reproductive technology (ART). Abbreviations : ART: assisted reproductive technology; IVF: in vitro fertilization; ICSI: intracytoplasmic sperm injection; TFF: total fertilization failure; TESA: testicular sperm aspiration.